Scenathon 2023 - Douzal, Clara; Chemarin, Charlotte; Mosnier, Aline; Orduña-Cabrera, Fernando; Jones, Sarah; Adenäuer, Lucie; Vittis, Yiorgos; Cozza, Davide; Diaz, Maria; Sanchez, Andrea; Navarrete Frias, Carolina; Obersteiner, Michael; et al. (Zenodo, 2024)
This database contains key parameters and variables from the 2023 Scenathon. The Scenathon is a participatory decision-making exercise that integrates models, stakeholders, and technology to address complex, multi-objective challenges. It allows country teams to iteratively adjust their assumptions and pathways, ensuring balanced trade flows and progressively enhancing ambition to meet global targets.